2014
DOI: 10.1016/j.icarus.2014.07.023
|View full text |Cite
|
Sign up to set email alerts
|

New insights into martian atmospheric chemistry

Abstract: 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…[37][38][39][40]42 HOCO is an important intermediate in combustion and atmospheric chemistry and it is also assumed to be involved in the formation of prebiotic molecules in the interstellar medium. [46][47][48][49][50] This radical has two conformers, the trans form being lower in energy than the cis form by about 500 cm À1 . It has been shown that trans-HOCO can be produced in low-temperature matrices upon photolysis or radiolysis of some CO-or CO 2 -containing intermolecular complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40]42 HOCO is an important intermediate in combustion and atmospheric chemistry and it is also assumed to be involved in the formation of prebiotic molecules in the interstellar medium. [46][47][48][49][50] This radical has two conformers, the trans form being lower in energy than the cis form by about 500 cm À1 . It has been shown that trans-HOCO can be produced in low-temperature matrices upon photolysis or radiolysis of some CO-or CO 2 -containing intermolecular complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we apply for the first time the computer algorithm PAP to the output of the updated version of the JPL/Caltech KINETICS model of the Martian atmosphere (Nair et al, 1994;Boxe et al, 2014) to identify all significant chemical pathways and quantify their contribution to O 3 formation and consumption up to 80 km altitude.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For the chemical pathway analysis, we used the steady state solution of the photochemical model for fixed temperature and pressure profiles (for details see Nair et al, 1994). The chemical reaction system includes 149 reactions (for details see Stock et al, 2012a;Boxe et al, 2014). In contrast to Stock et al (2012a), we distinguish between the excited state O 2 ( 1 ∆) and the ground state O 2 ( 3 Σ) of molecular oxygen.…”
Section: Martian Atmospheric Photochemical Column Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…3 While these atoms are mostly removed by quenching to the ground state through collisions with CO2, 4 a small fraction of these atoms react with H2 and H2O, present at trace levels generating OH radicals. 5 The subsequent reaction of OH radicals with CO acts to regenerate CO2, helping to maintain the stability of the Martian atmosphere.…”
Section: Introductionmentioning
confidence: 99%